A Rare Case of Pupillary Block Glaucoma Following CentraFLOW Implantable Collamer Lens Surgery. Issue 8 (August 2017) - Grover, Isha G.; Senthil, Sirisha; Murthy, Somasheila; Reddy, Jagadesh C.
Abstract : A 28-year-old lady with a refractive error of −11.0 D sphere/−1.50 D cylinder at 160 degrees in the right eye underwent an uneventful Implantable Collamer Lens surgery (ICL) with a V4c model, which uses a central Aquaport. This ICL does not require preoperative laser iridotomy or surgical iridectomy, as the centraflow opening is designed to prevent pupillary block. At postoperative day 1, her visual acuity in the right eye was 20/400, with diffuse microcystic corneal edema with fixed, dilated pupil and high intraocular pressure. Following intravenous mannitol, the corneal edema resolved. It was then noted that the ICL was anteriorly displaced, creating acute pupillary block, presumably due to obstruction of the central Aquaport with viscoelastic and inflammatory debris. She underwent AC wash the same day that helped in IOP control; however, the pupil remained permanently dilated and fixed because of extensive sphincter atrophy as a result of acute pupillary block. By 1 month, the visual acuity was 20/30 with an IOP of 14 mm Hg, which was maintained at 1-year follow-up. We report the first case of pupillary block glaucoma with this particular ICL design, suggesting the need for careful attention to complete removal of viscoelastic in the anterior chamber and behind the ICL, to prevent such complications and their cosmetically unacceptable sequelae.